Burnout: Redefining its key symptoms. (August 2021) - Tavella, Gabriela; Hadzi-Pavlovic, Dusan; Parker, Gordon
Highlights: Bifactor modelling was used to develop a new model of burnout. Our model expands on the dominant triadic model of burnout. Burnout may potentially be best defined as a unidimensional syndrome. Depression symptoms in burnout do not necessarily suggest synonymity of burnout and clinical depression. Abstract: Burnout is currently operationalised as comprising of exhaustion, depersonalization and reduced personal accomplishment. However, questions have been raised as to whether this three-factor model accurately characterises the syndrome. We therefore sought to re-examine burnout's key symptoms and to develop a new model of the syndrome. 622 participants who self-identified as experiencing burnout completed a questionnaire covering a large item set of candidate burnout symptoms. Bifactor modelling identified a 34-item general factor that was dominated by items capturing exhaustion and cognitive dysfunction, but which also included items indicative of decreased work performance, insularity and a depressed mood. Five specific factors capturing additional data variance were identified and were interpreted as representing cognitive impairment, empathy loss, exhaustion, compromised work performance, and social withdrawal. Reliability indices indicated that the general factor alone accounted for most of the variance in observed scale scores for each specific factor, except for the loss of empathy specific factor. We concluded that burnout may therefore potentially be modelled as a unidimensional construct comprising exhaustion, cognitive impairment, compromised work performance, empathy loss and social withdrawal. Further, while those with burnout are likely to experience depressive symptoms, their presence is not of necessity indicative of clinical depression.